Applying PBL to a Course on Measurements & Instrumentation - Case Study of Speed Sensing - Manam, Srikanth; Saravanan, M.; Srinivasulu Raju, S.; Santhosh Kumar, B.; Manideep, T. V. N.; Kavya, S. (Journal of Engineering Education Transformations, 2021)
This paper presents application of Project Based Learning â€“ PBL using design, simulation, and construction of hardware/software modules for Speed Measurement. Speed Measurement setup had been developed for demonstration in theory, laboratories and project demos for academia in measurements & instrumentation courses. A traditional measurement setup-Stroboscope that is commonly used for demonstration in laboratories is presented to serve as a base for comparison. The proposed speed measurement for laboratory is envisioned based on counting the number of state changes of a sensing switch. Different approaches and possibilities are discussed that could be implemented in student’s education. This approach is aimed at increasing knowledge, skill levels of students and help in using theoretical knowledge for application to practical & real-world problems. It also presents opportunities in instilling design thinking, skill development, integration and team work. Models based on only Software and ones that include hardware are presented for simulation & actual measurement. National Instruments â€“ NI’s software - LabVIEW, Multisim & hardware - myRIO & ELVIS ii+ are used for demonstrating different models presented here.